Uterine Leiomyosarcoma in a Young Unmarried Lady-A Case Report (Global Journal of Medical Research, 2022)
Leiomyosarcoma of the uterus is a very rare malignancy. It arises from the smooth muscles of the uterus. Very few cases on uterine leiomyosarcoma have been published so far. We report a case of a 23-year-old unmarried female who was having severe menorrhagia and was diagnosed later as a case of uterine leiomyosarcoma. The final diagnosis of leiomyosarcoma was made by histopathology. The only curative treatment of leiomyosarcoma of the uterus is surgery. The prognosis completely depends on the extension and histological characteristics like mitotic index, during the time of diagnosis.
Keywords: leiomyosarcoma of the uterus; menorrhagia; uterine malignancy